2022
DOI: 10.5603/cj.a2022.0106
|View full text |Cite
|
Sign up to set email alerts
|

Metal free percutaneous coronary interventions in all-comers: First experience with a novel sirolimus-coated balloon

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Interestingly, this study reported a relatively high rate of MACE in ISR lesions (14.9% vs. 4.9% in de-novo lesions) ( 20 ). In addition, we have recently published our early experience with another SCB, the Selution SLR™ (MedAlliance SA, Switzerland), in an all-comer CAD population, which had similar characteristics the current study cohort ( 16 ). There, the MACE rate at 1 year was slightly higher (6.8%).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Interestingly, this study reported a relatively high rate of MACE in ISR lesions (14.9% vs. 4.9% in de-novo lesions) ( 20 ). In addition, we have recently published our early experience with another SCB, the Selution SLR™ (MedAlliance SA, Switzerland), in an all-comer CAD population, which had similar characteristics the current study cohort ( 16 ). There, the MACE rate at 1 year was slightly higher (6.8%).…”
Section: Discussionmentioning
confidence: 71%
“…When interpreting our results, one needs to consider that we aim for vigorous lesion preparation, including cutting and/or non-compliant balloons at high pressure, in the majority of DCB cases treated at our site ( 16 , 22 , 23 ). The importance of such a strategy in order to achieve good long-term outcomes following DCB treatment has been shown before ( 5 , 16 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations